Faktor Anteseden Impulsive Buying: Studi Peran Mediasi Attitudinal Loyalty dan Moderasi dari Self-Control - Feby Elvaretta; Puji Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the digital age, impulse purchases, especially among millennials, are often influenced by promotions on social media and online shopping platforms. The purpose of this study is to understand the extent to which these factors contribute to OCE and impulse buying behavior. This study used a quantitative approach with a survey design through a Google Form questionnaire to 326 Shopee users in Jabodetabek, with data analyzed using Lisrel's Structural Equation Modeling (SEM). The results show that OCE has no direct impact on impulsive buying, while hedonic value has a significant influence. Attitudinal loyalty does not mediate the relationship between OCE and impulsive buying, and self-control can reduce impulsive buying tendencies. This research contributes to marketing strategies and customer relationship management in marketplaces, highlighting the need to improve the shopping experience to encourage impulsive buying while maintaining transaction security, product authenticity, and service quality. Promotional strategies, such as videos, can encourage impulsive buying without damaging consumer trust or loyalty. These findings confirm the importance of OCE in the sustainability of online businesses.